Current Legal Sociology : A Periodical Publication of Abstracts and Bibliography in Law and Society : Winter 2000 - Arnaud, André-Jean (edición) ((Current Legal Sociology ;)
Publicación periódica con resúmenes y bibliografía de sociología jurídica.